2004
DOI: 10.1007/s00259-004-1601-2
|View full text |Cite
|
Sign up to set email alerts
|

Variability of left ventricular ejection fraction and volumes with quantitative gated SPECT: influence of algorithm, pixel size and reconstruction parameters in small and normal-sized hearts

Abstract: In patients with a normal-sized heart, LVEF and volume estimates computed from different commercially available software packages for quantitative gated SPECT are well correlated. LVEF and volumes are only slightly sensitive to changes in matrix size. Smoothing, by contrast, is associated with significant changes in volumes but usually not in LVEF values. However, owing to the specific characteristics of each algorithm, software should not be interchanged for follow-up in an individual patient. In small hearts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…The parameters of both these reconstruction methods can modify the quantitative results of myocardial perfusion imaging (e.g., the LVEF) (4,7,10,11,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters of both these reconstruction methods can modify the quantitative results of myocardial perfusion imaging (e.g., the LVEF) (4,7,10,11,29).…”
Section: Discussionmentioning
confidence: 99%
“…For determination of a phantom's volumes and LVEF after reconstruction, QGS software has been shown to be fast (8) and reproducible (10,12) and gives LVEF values that compare well with those obtained by other reliable techniques (1,5,6,8,10). Nevertheless, it has been shown that QGS underestimates LV volumes (4,12,29,35), resulting in an overestimation of LVEF (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in patients with a relatively small left ventricular cavity, for instance in women or children, or with left ventricular hypertrophy, the endocardial border may be inaccurately identified, leading to underestimation of the end-systolic volume [46,47]. This causes significant overestimation of the left ventricular ejection fraction, although differences exist in the degree of overestimation using the various available processing algorithms [47,48]. It has been suggested that proper filtering and zooming may reduce the inaccuracy of gated SPECT in these subjects [46,47].…”
Section: Gated Spect Techniquementioning
confidence: 99%
“…This causes significant overestimation of the left ventricular ejection fraction, although differences exist in the degree of overestimation using the various available processing algorithms [47,48]. It has been suggested that proper filtering and zooming may reduce the inaccuracy of gated SPECT in these subjects [46,47]. In spite of the finding of very small values in females, a recent article has demonstrated that preserved left ventricular ejection fraction and normal left ventricular volumes have an incremental prognostic value over perfusion abnormalities in women as well as in men [49].…”
Section: Gated Spect Techniquementioning
confidence: 99%